Current situation of vocational training social work in Vietnam today (Revista de Investigaciones Universidad del Quindío, 2023)
The social work industry has been playing an important role in the development of equality and progress of each nation and mankind. In particular, the social work sector contributes to solving social issues related to the lives of individuals, small groups, and communities of disadvantaged people. Today, along with rapid economic growth, many pressing social issues are also on the rise. Therefore, addressing and preventing these social problems is very necessary, requiring a staff of social workers to solve the above problems. Therefore, the development and expansion of the scope of social work training is an urgent requirement and in line with the general development trend of the era. This article will focus on analyzing the current status of social work training in our country in the context of integration.
Keywords: Vocational training; Social Work; Educate; Reality; Vietnam